Teachers’ Perceptions and Challenges in Integrating Technology in English Reading Course: A Systematic Research Review - Herdina, Griseldis Faden; Ningrum, Ary Setya Budhi (Universitas Nusantara PGRI Kediri, 2023)
This study aims to analyze teachers' perceptions and challenges in integrating technology to teach English reading skills. This study uses a systematic analysis method that identifies existing literature on Google Scholar. Data collection was carried out through systematic literature review stages: 1) framing questions for a review, 2) identifying relevant work, 3) assessing the quality of studies, 4) summarizing the evidence, 5) interpreting the findings. The results of this study found that the teacher's positive perception of integrating technology in learning English and integrating technology can help teaching and learning activities and make classes interesting. The challenges faced by teachers in integrating technology include the lack of technology media facilities, slow internet connections, lack of teacher skills in mastering technology, teacher or student motivation to use technology in learning English, and proper material preparation. Based on these results, it can be concluded that teachers have a positive attitude towards integrating ICT in English learning activities, especially for teaching students' English reading skills.